2023
DOI: 10.3892/br.2023.1607
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease and cardiovascular involvement: Edifying insights (Review)

Abstract: Parkinson's disease (PD) is one of the most common neurodegenerative illnesses, and is a major healthcare burden with prodigious consequences on life-quality, morbidity, and survival. Cardiovascular diseases are the leading cause of mortality worldwide and growing evidence frequently reports their co-existence with PD. Cardiac dysautonomia due to autonomic nervous system malfunction is the most prevalent type of cardiovascular manifestation in these patients, comprising orthostatic and postprandial hypotension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…[ 16 ] A review of ECGs shows that QTC prolongation was significantly higher in non-survivor PD cases than in a control group. [ 17 ] In this research, we found that QT and QTc parameters were appreciably prolonged in the PD group than in the control group. QT and QTc parameters were positively correlated with Modified YHS.…”
Section: Discussionmentioning
confidence: 58%
“…[ 16 ] A review of ECGs shows that QTC prolongation was significantly higher in non-survivor PD cases than in a control group. [ 17 ] In this research, we found that QT and QTc parameters were appreciably prolonged in the PD group than in the control group. QT and QTc parameters were positively correlated with Modified YHS.…”
Section: Discussionmentioning
confidence: 58%
“…Our results suggest that underlying cardiovascular problems could be a risk factor for developing iPD, especially in males. This could be attributed to common disease-associated risk factors between CVD and PD, chronic inflammation because of the underlying cardiac problems or due to CVD induced vascular damage leading to reduced blood flow to the brain causing the neuronal death [ 29 , 30 ]. Therefore, CVD history as a risk and sex-specific differences must be taken into account when assessing patients with suspected iPD and developing preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…This temporal response of symptoms to DBS can be related to a number of factors including the change in medications after surgery and the underlying disease progression. Indeed, levodopa and dopaminergic medications in general are known to have an effect on cardiovascular functions in PD [ 57 ], with higher doses having a more detrimental effect than lower doses [ 58 ]. The reported short-term improvement in cardiovascular symptoms after DBS may reflect the decrease in total levodopa equivalent daily dose (46.9% reduction in the included studies), however only scanty data are available and there is no control for this variable in the vast majority of the studies.…”
Section: Discussionmentioning
confidence: 99%